2005
DOI: 10.1056/nejmoa043470
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon Alfa-2a, Lamivudine, and the Combination for HBeAg-Positive Chronic Hepatitis B

Abstract: In patients with HBeAg-positive chronic hepatitis B, peginterferon alfa-2a offers superior efficacy over lamivudine, on the basis of HBeAg seroconversion, HBV DNA suppression, and HBsAg seroconversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
1,400
13
46

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,410 publications
(1,541 citation statements)
references
References 35 publications
72
1,400
13
46
Order By: Relevance
“…Subsequent follow-up showed that the loss of HBsAg differed according to HBV genotype: 14% for genotype A, 9% for genotype B, 3% for genotype C, and 2% for genotype D (A vs. D: P = 0.006) [112]. In another multicenter phase 3 trial using a standard dose of pegylated IFN-a 2a for 48 weeks, genotype A patients had the highest HBeAg seroconversion rate (50%) but the difference between genotype B and C patients was not significant (30% vs. 31%) [113]. In a recent randomized controlled trial from China, Zhao et al assessed the efficacy of low-dose, 24-week IFN or pegylated IFN treatment as well as factors predicting sustained response in patients with HBeAgpositive chronic hepatitis B [114].…”
Section: Genotypesmentioning
confidence: 96%
“…Subsequent follow-up showed that the loss of HBsAg differed according to HBV genotype: 14% for genotype A, 9% for genotype B, 3% for genotype C, and 2% for genotype D (A vs. D: P = 0.006) [112]. In another multicenter phase 3 trial using a standard dose of pegylated IFN-a 2a for 48 weeks, genotype A patients had the highest HBeAg seroconversion rate (50%) but the difference between genotype B and C patients was not significant (30% vs. 31%) [113]. In a recent randomized controlled trial from China, Zhao et al assessed the efficacy of low-dose, 24-week IFN or pegylated IFN treatment as well as factors predicting sustained response in patients with HBeAgpositive chronic hepatitis B [114].…”
Section: Genotypesmentioning
confidence: 96%
“…Immunoreactivity is represented by high levels of ALT, low levels of HBV-DNA and high necroinflammatory activity at histological analysis. High pretreatment ALT levels and low HBV-DNA levels are associated with higher rates of seroconversion with interferon treatment 45,46,48,49 and also associated with responses to PEG-IFN alpha-2a in HBeAg-negative patients; ALT > 5 -fold the upper limit of normality (ULN) was the most important predictor of combined response (ALT normalization, HBV-DNA suppression) in week 24 postreatment. 50 Quantitative HBsAg has recently become an important area of scientific interest.…”
Section: Pretreatment Predictors Of Response To Peg-ifnmentioning
confidence: 99%
“…44 The HBV genotype A, prevalent in Western Europe and America, is also associated with higher rates of response to treatment with interferon. [45][46][47] In Asia and the Pacific regions, genotypes B and C are more prevalent and there is a controversy whether there is any difference regarding their response to interferon. 15,45,46 Based on the results of well-designed studies, patients with good immunoreactivity tend to respond better to interferon.…”
Section: Pretreatment Predictors Of Response To Peg-ifnmentioning
confidence: 99%
“…PegIFN-a therapy results in HBeAg seroconversion rates of up to 32% and 48%, respectively, when assessed at weeks 24 and 48 post-treatment [43][44][45][46] and sustained after cessation of therapy in the majority (80-90%) of HBeAgpositive patients [47]. Baseline HBV and ALT levels are predictive factors for HBeAg seroconversion [47].…”
Section: Treatment-induced Hbeag Seroconversion and Disease Progressionmentioning
confidence: 99%